STUDY OF PREVALENCE OF SEVERE COMMUNITY-ACQUIRED PNEUMONIA IN PATIENTS HAVING DIABETES MORE THAN 1 YEAR ADMITTED TO A TERTIARY CARE HOSPITAL IN EASTERN INDIA: A RETROSPECTIVE COHORT STUDY. - Malik, Manaranjan; Pathi, Debasis; Mishra, Subhashree; Pattnaik, Sidharth S (Student's Journal of Health Research Africa, 2025)
Aim This study aims to assess the prevalence of CAP among diabetic patients receiving treatment at a tertiary care hospital in Bhubaneswar. Methods This retrospective study was conducted at KIMS and PBMH, Bhubaneswar, analyzing hospital records of 100 diabetic patients with CAP over one year (April 1, 2023, to April 1, 2024). Data were collected on demographics, clinical history, and laboratory findings, and analyzed using SPSS version 25. Results The majority of participants were aged over 60 years, with a higher prevalence of CAP in uncontrolled diabetes (48%) than in controlled diabetes (45%). Urban residents were predominant in both groups, though low-income individuals had poorer diabetes control. Uncontrolled diabetic patients exhibited more severe symptoms, higher RBS and ESR levels, increased pleural effusion, and longer hospital stays. Conclusion Uncontrolled diabetes is associated with a marginally higher prevalence of CAP and increased disease severity. Socioeconomic factors, and glycemic control play a crucial role in patient outcomes. Recommendation It is recommended that improving glycemic control and addressing socioeconomic factors be prioritized in managing diabetic patients to reduce the prevalence and severity of CAP.